Laser induced nano-patterning with atomic-scale thickness on an InAs/GaAs surface. (19th October 2018) - Zhang, Wei; Shi, Zhenwu; Yang, Xinning; Chen, Chen; Yang, Linyun; Zeng, Zhongming; Zhang, Baoshun; Liu, Qian
Abstract: Nano-patterned substrates fabricated by different techniques have been widely applied in high performance semiconductor devices. For the influence of surface morphology on semiconductor electronic properties and epitaxy growth, there is an increasing interest to realize atomic-scale surface modification by a simple and effective method. In this study, laser induced nano-patterning with atomic-scale thickness on an InAs/GaAs surface was studied in both atmosphere and vacuum environments. Periodic nano-grooves with an average depth of 1 to 2 atomic layers were fabricated by focused laser spot scanning in the air. The depth and width of nano-grooves increase with the laser energy intensity. The result of nano-patterning is attributed to atom desorption stimulated by photon-induced electronic excitation. To explore the situation in the vacuum, in situ two-beam laser interference was applied during InAs/GaAs sample MBE growth. Periodic InGaAs nano-islands were fabricated, which show significant influence on subsequent crystal growth. The formation of ordered InAs quantum dots agreeing with the atomic layer nano-pattern demonstrates the potential application of the technique in site-controlled quantum dot growth.